2004
DOI: 10.1091/mbc.e03-08-0584
|View full text |Cite
|
Sign up to set email alerts
|

The Bone Morphogenetic Protein Type Ib Receptor Is a Major Mediator of Glial Differentiation and Cell Survival in Adult Hippocampal Progenitor Cell Culture

Abstract: Bone morphogenetic proteins (BMPs) act as growth regulators and inducers of differentiation. They transduce their signal via three different type I receptors, termed activin receptor-like kinase 2 (Alk2), Alk3, or bone morphogenetic protein receptor Ia (BMPRIa) and Alk6 or BMPRIb. Little is known about functional differences between the three type I receptors. Here, we have investigated consequences of constitutively active (ca) and dominant negative (dn) type I receptor overexpression in adultderived hippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 57 publications
4
19
0
1
Order By: Relevance
“…Whereas ALK3 and ALK6 phosphorylates Smad1, 5, and 8, ALK2 only phosphorylates Smad1 and 5 under physiological conditions [44]. In addition, ALK3 signaling has a functionally different effect from that of ALK2 and 6 on cellular apoptosis of hippocampal progenitors [45]. These studies can support our results that the effect of ALK2 on iPSC generation is different from that of ALK3.…”
Section: Discussionsupporting
confidence: 84%
“…Whereas ALK3 and ALK6 phosphorylates Smad1, 5, and 8, ALK2 only phosphorylates Smad1 and 5 under physiological conditions [44]. In addition, ALK3 signaling has a functionally different effect from that of ALK2 and 6 on cellular apoptosis of hippocampal progenitors [45]. These studies can support our results that the effect of ALK2 on iPSC generation is different from that of ALK3.…”
Section: Discussionsupporting
confidence: 84%
“…We therefore conclude that BMPR1a mediates suppressive effects of BMPs on oligodendroglial progenitors. However, a previous study has reported that overexpression of dominant-negative (dn) BMPR1b, but not dnBMPR1a, in cultured adult hippocampal progenitors increases immature oligodendroglial numbers (Brederlau et al, 2004). This is in contrast to our findings, possibly reflecting differences between our in vivo data and the in vitro data in that study, differences between developing animals and the adult cells used in that study, or examination in that study of a restricted subset of hippocampal progenitor cells that do not normally generate the major populations of oligodendrocytes in the brain.…”
Section: Discussionmentioning
confidence: 96%
“…BMPs bind to heteromeric receptors formed by type I (BMPR1a, BMPR1b, Alk2) and type II (BMPRII) subunits (Koenig et al, 1994;ten Dijke et al, 2003). Several studies suggest that BMPR1b mediates the effects of BMPs on exit from cell cycle and terminal differentiation of progenitor cells (Panchision et al, 2001;Gulacsi and Lillien, 2003;Brederlau et al, 2004). However, null mutation of BMPR1b produces no apparent phenotype in the nervous system (Yi et al, 2000), whereas loss of BMPR1a leads to abnormal early forebrain development (Davis et al, 2004) and loss of choroid plexus later in development (Hebert et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As a control, we show the additive effect found when GM6001 was applied together with noggin (Fig. 1J), which decreases gliogenesis by a different mechanism, implying bone morphogenetic protein (BMP) inhibition [12,42,43] Neural Precursors from Postnatal SVZ Expressed Several ADAMs and EGFR Ligands and Released TGF-a Through a Metalloprotease-Mediated Mechanism…”
Section: Inhibition Of Egfr or Metalloprotease Activity Promoted Neurmentioning
confidence: 89%